1960
DOI: 10.1002/jsfa.2740111213
|View full text |Cite
|
Sign up to set email alerts
|

Insect control by gamma‐irradiation: An appraisal of the potentialities and problems involved

Abstract: Experimental sources of cobalt‐60, made radioactive by neutron irradiation, have been used during recent years for investigating the radiation susceptibility of insect pests. Lethal and sterilising effects have been examined on species, strains and developmental stages to evaluate the dose levels required for commercial treatment. The technical feasibility of using radiation as an insecticide is now established. Results of research and problems of application are examined in relation to the two potential metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…), was actually eradicated on the island of Curacao through the release of adults sterilized by gamma radiation (Baumhover et al, 1955;Lindquist, 1955). Further discussions of the main factors that affect the success of insect control by this measure were published by Knipling (1959Knipling ( , 1960, Bushland (1960), Cornwell and Bull (1960), and von Borstel (1960).…”
Section: Introductionmentioning
confidence: 99%
“…), was actually eradicated on the island of Curacao through the release of adults sterilized by gamma radiation (Baumhover et al, 1955;Lindquist, 1955). Further discussions of the main factors that affect the success of insect control by this measure were published by Knipling (1959Knipling ( , 1960, Bushland (1960), Cornwell and Bull (1960), and von Borstel (1960).…”
Section: Introductionmentioning
confidence: 99%
“…Another effect of irradiation is a direct effect on gametes in the body of a normal adult. Thirdly, the adult insects may not take part in normal sexual activities (Cornwell and Bull, 1960).…”
Section: Radiation Effects On Insectsmentioning
confidence: 99%
“…Seasonal production, fluctuation in demand, and good and bad harvests will operate against the efficient use of irradiation (Cornwell and Bull, 1960).…”
Section: Radiation As An Insecticidementioning
confidence: 99%
“…The investigations covered mode of action of radiation on insect tissues; dose levels for immediate death or reproductive sterilization, effects of radiation on the materials treated; and the development of apparatus in which grain might be treated on a commercial scale. It was shown that a dose of 16,000 rads was adequate to effect reproductive sterilization of all species studied; that this dose had no effect on the milling or baking quality of wheat or had any other deleterious effects; and that it could be applied economically under practical conditions, either by 6oC0 y-radiation or accelerated electrons (Cornwell & Bull, 1959).…”
Section: A T the Atomic Energy Research Establishmentmentioning
confidence: 99%